2008
DOI: 10.1002/adma.200801291
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Motor‐Powered Self‐Assembly of Dissipative Nanocomposite Rings

Abstract: Thermodynamic relaxation can generate complex nanostructured materials via self-assembly; these structures, however, are ultimately limited by chemical equilibria and diffusional transport processes. [1] In contrast, living systems use a concerted combination of thermodynamic and energydissipating processes to remove these functional limitations, and generate complex, structured materials with a wide range of adaptive and emergent behaviors. An underlying principle of such systems involves the dynamic self-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 23 publications
5
79
0
Order By: Relevance
“…Such relaxation would highlight the dynamic nature of microtubule assembly, as suggested by the presence of a metastable stage at the fastest transport velocity (~15 min in Fig. 2b, iii; reported previously 26 ). However, we did not detect any substantial difference in spool circumference over the same time course (~15 min vs. >60 min, Fig.…”
Section: Transport Velocity Influences Spool Size During Initial Assesupporting
confidence: 69%
“…Such relaxation would highlight the dynamic nature of microtubule assembly, as suggested by the presence of a metastable stage at the fastest transport velocity (~15 min in Fig. 2b, iii; reported previously 26 ). However, we did not detect any substantial difference in spool circumference over the same time course (~15 min vs. >60 min, Fig.…”
Section: Transport Velocity Influences Spool Size During Initial Assesupporting
confidence: 69%
“…Previous studies have observed the formation of microtubule 'spools' created using microtubule-gliding assays and cross-linked microtubules that bundle together (Liu et al 2008, Hess et al 2005, Kawamura et al 2008, 2010b, 2010a. The likely mechanism of spool formation appears to be pinning of a bundle on a dead kinesin in the gliding chamber that allows for high curvature and then cross-linking of the bundle to itself (Hess et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Among them, the ring-shaped assembly have been attracting considerable attention and appears to be a promising candidate for application in nanotechnology as this non-equilibrium structure is capable of storing a huge amount of bending energy 8 and can provide continuous work without changing the position of the mass center. [12][13][14][15][16] Therefore, it is important to understand how different factors affect the formation and properties of ring-shaped MT assemblies such as rotational direction, thickness (subtraction of inner diameter from outer diameter), size etc.. So far, we have successfully controlled the rotational direction 17 and thickness 18 of the ring-shaped MT assembly by tuning helical structure of MTs and by feeding MTs in a stepwise manner in the AcSO respectively.…”
Section: Introductionmentioning
confidence: 99%